Development of in Vitro Conservation Protocol for Banana Germplasm through a Slow Growth Technique - Obse Zewde (ASTU, 2023)
The study mainly focused on to development of an in vitro conservation protocol for three randomly selected banana varieties through a slow growth technique. Banana (Musaspecies) is one of the most important fruit crops grown widely in Ethiopia and it plays a huge role in the rural communities by ensuring food security, generating income and creating job. They are the fourth most important food crops after rice, wheat, and Maize. Globally, the major banana producing countries are India, China, Brazil, Ecuador and Philippines. In Africa, Angola, Tanzania, Kenya, Brundi and Cameron are the major banana producers. Major producers of banana in Ethiopia are found in Southern and south western Ethiopia, with 59.64% (53,956.13 ha) of the total fruit area and 68% (478,251.04 ton). Field conservation of vegetative propagated crops such as banana is a key concern for germplasm curators Nowadays, slow growth storage (SGS) technique becomes an economical in vitro method to preserve several plant species by controlling the growth and development of plantlets. As a procedure surface sterilized shoot tip meristem of about one-centimeter square explants were inoculated on Murashige and Skoog (MS) medium supplemented with plant growth regulator (PGR) and different types of plant growth retardant (PGR) such as manitol, sorbitol and sucrose SGR at sorbitol and manitol 0.2,0.3, 0.5 and Manitol 0.3, 0.5, 0.7 concentration was found to be the best for long storage of banana varieties under in vitro condition.ANOVA revealed existence of significant difference among varieties, confirming the need to develop varieties specific protocols. The contaminated and survived per cent among the varieties are Poyo 13.3, Giant 8.90, Grande 20.0 per cent are contaminated and the survival rate are in Poyo 86.70, Giant 91.10, Grande 80.00 percent are survived in each variety and treatment. The generated plantlets had survived for 3, 6 and 9 months. Therefore, the present study successfully designed an in vitro preservation technique for banana to safeguard its biodiversity.
Keywords: ANOVA, Banana, In vitro conservation, Plant growth retardant, Slow growth storage.